Effects of Different Organic Fertilizers on Yield and Yield-Related Characteristics in Black Cumin (Nigella sativa L.) Cultivation Under the Ecological Conditions of Tokat, Türkiye - Abdulkadir Acar; Yasin Bedrettin Karan (Turkish Journal of Agriculture: Food Science and Technology)
This research was carried out during the 2022 and 2023 growing seasons on Agricultural Research and Application Fields of Tokat Gaziosmanpaşa University. The study aimed to investigate the effects of different organic fertilizers and application rates on the yield and yield-related characteristics of black cumin (Nigella sativa L.). The experiment was designed using a split plot arrangement in a randomized complete blocks design with three replications. The main plots were assigned to five organic fertilizer types: Leonardite, Vermicompost, Solid Humus, Chicken Manure and Sheep Manure, while the subplots included in the same way in all fertilizer forms four fertilizer doses (0, 150, 300 and 600 kg/da). The study utilized “Çameli” variety, the only registered Nigella sativa L. variety in Turkiye. Key parameters examined over both years included plant height (cm), number of branches per plant (number), number of capsules per plant (number), number of grains per capsule (number), thousand seed weight (g), seed yield (kg/da). The results; revealed that the average plant height ranged from 39.76 to 54.33 cm, the number of branchers per plant, ranged from 6.22 to 6.35, the number of capsules per plant ranged from 13.43 to 14.88, the number of seed per capsule ranged from 98.56 to 104.00, thousand seed weight varied between 2.50 and 3.11 g, seed yield ranged from 135.26 to 135.41 kg/da. Statistically significant differences (p<0.01) were observed for all examined characteristics. Based on the two-year results the application of chicken manure at 300 kg/da was identified as the most effective treatment, significantly enhancing plant height, capsule number and thousand seed weight. This finding reveals that the use of organic fertilizer in black cumin cultivation is an important alternative for farmers who want to both increase yield and prefer a natural production method.